INCOME ANALYSIS OF BALI DUCK FARM FATTENING WAS CONTAINED RATION WITH MUNGBEAN WASTE FERMENTED - A. M. N, SONGKAM; PUTRI, B. R. T.; SITI, N. W. (Majalah Ilmiah Peternakan; Vol 24 No 1 (2021): Vol. 24 No. 1 (2021), 2021)
The aim of this study was to determinated the income analysis of bali duck farm fattening was contained ration with mungbean waste fermented. This research was conducted during eight weeks at Raya Sesetan Street Markisa alley no. 5 Faculty of Animal Husbandry Udayana University, South Denpasar District, Denpasar City. The study designed with a complately randomized design (CRD) with 3 treatments and 5 replications, with quantity of bali ducks used 45 heads. The treatments of research were bali duck with commercial ration 100% (P0), commercial ra- tion replaced with mungbean sprout waste fermented 12,5% (P1), and commercial ration replaced with mungbean sprout waste fermented 25% (P2). The research variable is income analysis of bali duck fattening was seen based on cost, revenue, income, R/C ratio and BEP. The results income analysis of bali duck fattening was replaced with mungbean sprout waste fermented 12,5% gives the best results with a net benefit Rp 37.062,-/period or 1.671/kg body weight with the value of R/C ratio is 1,039, BEP units of production 20,63 kg body weight, BEP price is Rp 40.716,-/kg body weight and BEP revenue is Rp 876.574,-/period. Based on the results of the study it can be con- cluded that additional contained ration with mungbean waste fermented could it be increase income of bali duck farm fattening.